The Bible and Sexuality in Netflix’s Coming Out Colton: ‘There’s a Lot to That Book’ - Neutel, Karin B. (Lectio difficilior, 2024)
Popular and academic discussions about ‘the Bible and homosexuality’ often centre on a small but consistent number of passages from the Old and New Testaments. Given this consistency, the conversations around sexuality and Christian faith in the Netflix series Coming Out Colton are remarkable for not referencing any of these texts, while still repeatedly mentioning the Bible in general, as well as specific biblical texts. The show opens up a small but significant window into the range of ways in which biblical texts are currently used and given meaning and authority in connection with sexuality. The show confirms the tendency observed in previous research that contemporary Bible users who operate in a digital context are interested specifically in ‘therapeutic’ texts and uses of the Bible, at the expense of ‘propositional’ ones. Given the show’s wide audience, the presentation of the Bible in it can be expected to have an influence in shaping how biblical texts will be seen and used in conversations about sexuality in the near future. This may mean that appeals to the Bible in the context of sexuality will increasingly be more fluid and therapeutic, and move away from the ‘clobber texts’ that have often dominated this discourse.